The influence of online reviews on the purchase decisions of customers in luxury fashion - Gato, Ana Carolina Lopes (2024)
Dissertation presented as the partial requirement for obtaining a Master's degree in Data Driven Marketing, specialization in Digital Marketing and Analytics